PENGARUH KUALITAS PELAYANAN, HARGA DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN TRANSPORTASI OJEK ONLINE GRAB - Saragih, Dia Putra; Ulfah, Maria; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this study was to ascertain the effect of service quality, pricing, and brand image on customer satisfaction when FKIP UNTAN students use online Grab transportation.The research approach employed was quantitative research employing survey methods. 62 Fkip Untan students who had utilized the Grab website at least twice were included in this survey. A questionnaire is employed as the instrument. Multiplle linear regression analysis was used to examine the data in SPSS version 20. Wii th a Tcount of 2.693 Ttable of 2.001 and a significance value of (0.009 0.05), thie results showed that service quality had a favorable and substantial impact on customer satisfaction among FKIP Untan students who utilized Grab online transportation. Witth a Tcount of 2.330 Ttable of 2.001 and a significance value of (0.023 0.05), price has a positive and substantial impact on consumer satisfaction when FKIP Untan students use Grab online transportation. Witih a Tcount of 3.954 Ttable of 2.001 and a significance value of (0.000 0.05), brand image has a favorable impact on customer sati sfaction when FKIP Untan students use Grab online service. Simultaneously, the quality of servicie, price, and brand image affect consumer satisfaction using Grab online transportation among FKIP Untan students, with a Fcount of 21.146 Ftable of 2.76, a "˜significance value of (0.000 0.05), and a coefficient of determination (R2) of 0.522 (52.2%).